The biochemistry of DNA and RNA 1: chemistry - Houston, Douglas (Henry Stewart Talks, 2019)
The structure of DNA, Types of binding between molecules, Van der Waals non-covalent bonds, Hydrogen bonds, Amino acid side chain hydrogen bonding, Salt bridges, Zinc fingers